Improving Eleventh-Grade MA YPPI Students’ Vocabulary Mastery Through the Mind Mapping Learning Method - Mutmainnah Marzuki; Sri Reski Amalia; Andi Anugerah M; Fahmi Room (Pendidikan Nonformal Universitas Muhammadiyah Bulukumba, 2025)
This research aimed to determine the effectiveness of the Mind Mapping method in improving the vocabulary mastery of eleventh-grade students at MA YPPI Bulukumba. The study employed a pre-experimental design using one group pre-test and post-test involving 15 students selected through total sampling. A vocabulary-based multiple-choice test was used as the research instrument. Results showed a significant improvement in students’ vocabulary mastery after being taught using the Mind Mapping method. The mean score increased from 56.07 in the pre-test to 88.00 in the post-test. The t-test value of 18.33 exceeded the t-table value of 1.761 at a 0.05 significance level, indicating a significant difference between both tests. The findings conclude that the Mind Mapping method is effective in improving students’ vocabulary mastery.